The Influence of Co-Ligands on Improving Tumor Targeting of 99mTc-HYNIC Conjugated Peptides - Atekeh Torabizadeh, Seyedeh; Jalal Hosseinimehr, Seyed (Mini Reviews in Medicinal Chemistry, 2017)
Technetium-99m (99mTc) is widely used as a radionuclide for labeling of biomolecules in nuclear medicine practice. 6-hydrazinopyridine-3-carboxylic acid namely HYNIC is one of the best bifunctional chelating agents for attachment of 99mTc to the biomolecules such as peptides and proteins. Since HYNIC can only occupy one or two coordination sites of 99mTc, co-ligands are needed to complete the coordination sphere of the technetium. Selection of co-ligands can be impressive on the stability, lipophilicity and biodistribution of 99mTc-HYNIC conjugated peptides. The aim of this review was to explain the chemical and biological effects of various co-ligands on characteristics of 99mTc-HYNIC conjugates for tumor or diseases imaging.
Keywords: 99mTc